2009
DOI: 10.3892/ijo_00000417
|View full text |Cite
|
Sign up to set email alerts
|

Cepharanthine inhibits angiogenesis and tumorigenicity of human oral squamous cell carcinoma cells by suppressing expression of vascular endothelial growth factor and interleukin-8

Abstract: Abstract. Cepharanthine is a biscoclaurine alkaloid extracted from Stephania cepharantha Hayata, which is widely used for the treatment of many acute and chronic diseases, and can exert antitumor effects on several human cancer cell lines. However, little is known about the detailed mechanisms of the antitumor activity of Cepharanthine. In the present study, we determined whether Cepharanthine could suppress angiogenesis and growth of human oral squamous cell carcinoma (OSCC) cells in vitro and in vivo. Cephar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 30 publications
0
52
0
1
Order By: Relevance
“…The inflammatory pathways that are important in carcinogenesis include NF-κB, STATs and COX -, and they are promising targets for cancer therapy [31,32] . Previous studies have shown that inactivation of NF-κB is an important mechanism for the antitumor activity of CEP [8,15,16] . SaOS2 is an osteosarcoma cell line in which STAT3 is constitutively activated and plays a crucial role in cell proliferation and survival [10,22,33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflammatory pathways that are important in carcinogenesis include NF-κB, STATs and COX -, and they are promising targets for cancer therapy [31,32] . Previous studies have shown that inactivation of NF-κB is an important mechanism for the antitumor activity of CEP [8,15,16] . SaOS2 is an osteosarcoma cell line in which STAT3 is constitutively activated and plays a crucial role in cell proliferation and survival [10,22,33] .…”
Section: Discussionmentioning
confidence: 99%
“…Although accumulating evidence has shown that CEP plays a potential role in inhibiting cell growth and inducing apoptosis in many tumors [3] , the underlying mechanism remains elusive. Because CEP is primarily an anti-inflammatory agent, the antitumor activity of CEP is associated with inhibition of inflammation-related signaling pathways, among which NF-κB inactivation is important [8,15,16] . In addition to NF-κB, the signal transducer and activator of transcription protein 3 (STAT3) is another critical inflammatory mediator that links inflammation and cancer [17] .…”
Section: Introductionmentioning
confidence: 99%
“…It is a prognostic factor and is highly expressed in metastatic cancers, including NPC (22,23). IL-8 is proangiogenic (24) and contributes to a poor prognosis in primary NPC (25). IL-8 has been reported to increase expression of the antiapoptotic protein Bcl-2 in endothelial cells (26) and thus to maintain the angiogenic phenotype of endothelial cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is supported by the recent report that inactivation of Akt by a dominant negative form of Akt could result in suppression of MMP secretion thus suppression of in vivo pulmonary cancer metastasis. 28 Recently, Harada et al 29 also reported that decreased expression of Akt phosphorylation and FGF-2 was correlated with decreased tumorigenicity and angiogenesis in vivo and such reduced angiogenesis was partly due to the blockade of Akt1 activity. Our results also demonstrated that suppression of Akt1 activity by lentivirus-mediated CTMP overexpression might be responsible for inhibition of tumor progression.…”
Section: Lentivirus-mediated Ctmp Gene Transfection S-k Hwang Et Almentioning
confidence: 98%